The Role Of CSR On Green Accounting, Environmental Performance, Share Ownership And Eco Control And Their Impact On Corporate Financial Performance - Roro Endah Kumalasari; Nita Yura Roslina; Maulana Yusup (LPPM STMIK Mardira Indonesia, 2025)
This study aims to evaluate the impact of Green Accounting, Environmental Performance, Share Ownership, and Eco Control on Corporate Financial Performance, with Corporate Social Responsibility serving as an intervening variable, across companies in the Basic and Chemical Industry Sector from 2020 to 2024. The specific objective is to conduct an in-depth analysis of CSR, particularly in the basic and chemical industries, where effective implementation of Green Accounting and Eco Control can yield significant benefits for various stakeholders. This research employs secondary data, specifically PROPER, Annual Reports, and Sustainability Reports. The employed sampling strategy is purposive, and data analysis is conducted in EViews, with intervening data processed using the Sobel method. The findings of this study indicate that green accounting, environmental performance, and eco control influence CSR, whereas share ownership does not. In the subsequent analysis, green accounting, environmental performance, and eco-control do not affect CFP, whereas share ownership and CFP have a reciprocal effect on CFP. The Sobel test indicates that the CSR variable does not mediate the effects of green accounting, environmental performance, share ownership, and eco-control on Corporate Financial Performance.